Analisis Kinerja Finansial Pemerintah Daerah Provinsi DKI Jakarta Periode 2017-2021 - Stellavia Claudia Santosa; Andrew Pandowo; Agus Munandar (Jurnal Akuntansi, 2023)
This research aims to analyze the financial performance of DKI Jakarta by the government from 2017 to 2021. Research performance is conducted by calculating analysis ratio with five measurements namely independency ratio, efficiency ratio, effectiveness ratio, growth ratio and degree of decentralization. Results of this research show that there is high independence of the DKI Jakarta government, subsequently the government is rated effective in realizing regional revenue, also having significant growth and positive financial efficiency by the government. Keywords: Decentralization, Financial Performance, SiLPA